DIAMOND FROM THE LOS COQUITOS AREA, BOLIVAR STATE, VENEZUELA - Kaminsky F.V.; Zakharchenko O.D.; Khachatryan G.K.; Griffin W.L.; Channer D.M.Der. (My University, 2006)
A set of 77 diamond crystals from the Los Coquitos placer on the Guaniamo River in Bolivar State, Venezuela, has been comprehensively studied and compared to previously studied diamond from the Quebrada Grande kimberlite sills and placer deposits, both located 50 km to the southeast. The diamond crystals in the Los Coquitos placer are generally similar to those of the Quebrada Grande area, but with significant morphological differences. Diamond from the Los Coquitos placer has a higher total nitrogen content (Ntot = 719 at.ppm versus 614-706 at.ppm in diamond from Quebrada Grande) and a lower level of nitrogen aggregation (% NB = 65 versus 68 in diamond from Quebrada Grande). Carbon isotope values, δ13C, of the Los Coquitos diamond vary from +0.4 to -20.5‰, compared with -3.2 to -28.7‰ in the Quebrada Grande diamond. In the Los Coquitus suite, mineral inclusions in diamond are characterized by a lower Ca content in garnet, wider compositional variations in pyroxene (mg in the range 0.683-0.849), and lower Fo component in olivine (mg in the range 0.926-0.932), compared to inclusions in diamond in the Quebrada Grande suite. Los Coquitos diamond shows greater depletion in LREE compared to Quebrada Grande diamond. Diamond crystals at Los Coquitos were derived, at least in part, from a new, undiscovered kimberlite source in the Guaniamo River basin. These rocks are similar in type to the Quebrada Grande kimberlites, but were sampled from a different section of the subcontinental lithospheric mantle. The existence of two separate populations of diamond, each with its own primary source, suggests that other localities of placer diamond in Venezuela may have their own local source.
Keywords: CARBON ISOTOPES; DIAMOND; GUANIAMO; INFRARED SPECTRA; LOS COQUITOS; VENEZUELA